In-situ non-destructive analysis of Etruscan gold jewels with the micro-XRF transportable spectrometer from CNA. (December 2017) - Scrivano, S.; Ruberto, C.; Gómez-Tubío, B.; Mazzinghi, A.; Ortega-Feliu, I.; Ager, F.J.; Laclavetine, K.; Giuntini, L.; Respaldiza, M.A.
Abstract: The study of valuable Cultural Heritage objects frequently requires non-destructive analysis with good sensitivity. Moreover, it is often necessary that the measures are carried out in-situ, in particular when transport of the items from the institutions to the laboratory is not allowed. In this work, the technical specifications of the micro-XRF spectrometer developed at the CNA in Seville is presented and its analytical capabilities are tested by means of the analysis of a set of Etruscan gold jewels of the National Archaeological Museum of Florence. Since these jewels are characterized by elaborate decorations, with details of typical dimensions down to tens of microns, a high lateral resolution is required to study the features of these objects. The challenge consists in the characterization of the welding/soldering zones and the details of the jewels that present a very complex geometry. This paper shows the micro-XRF in-situ analysis of 15 Etruscan gold jewels (from the VII century BCE) in order to characterize the alloy composition of sheets, threads, filigrees, granules, as well as the joining zones. Based on these results, the manufacture technique and the production process employed by the Etruscan goldsmiths could be described. Highlights: A micro-XRF portable spectrometer developed for the study of Cultural Heritage materials is presented. The analytical capabilities of the device are tested by means of the study of 14 Etruscan gold jewels and a false fibula. The results of the archaeological samples show the use of three different joining methods, the most common being the copper salt diffusion bonding. The importance of the use of a micro beam in the study of ancient jewelry is evidenced by the results obtained for the forged fibula.